IN VITRO ANTICONVULSANT EFFECT OF ETHYL ACETATE FRACTION OF TITANUS LEAF (LEEA AEQUATA L.) ON ISOLATED COLON - Suwarso, Edy; Ginting, Nahitma; Sudarmi, Sudarmi; Manurung, Vegi Dwinata (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The excessive activity of the parasympathetic nervous system in the intestinal smooth muscle is important role in the increased intestinal motility, so antispasmodic medications are needed that can decrease intestinal motility such as atropine. Treatment may also use medicinal plants that are cheaper and easy to obtain, and also believed to have smaller side effects than modern antispasmodic drugs. This study aimed to determine the anticonvulsant or relaxation effects of the ethyl acetate fraction of titanus leaf (EAFTL) against contracted guinea pig colon. Methods: The parameters measured are smooth muscle relaxation. Before testing, guinea pig colon was equilibrated for 45 min to obtain a stable condition in Tyrode's solution with a temperature of 37°C aerated with carbogen gas (O2:CO2) with a ratio of 95%:5%. The relaxing effect of the colon was tested after inducing by acetylcholine chloride; then, each colon was given cumulative concentration of EAFTL and atropine sulfate. The concentration of acetylcholine chloride required to increase the contraction of the guinea pig colon was 1.76×10−4 Mol. The cumulative concentration of EAFTL given was 0.5–4 mg/Ml and cumulative concentration of atropine sulfate given was 6.95×10−6–2.08×10−2 mg/Ml. Results: The EAFTL has a relaxing effect. Statistical analysis of EAFTL at a concentration of 4 mg/Ml (100.000±1.7417) in reducing the smooth muscle of colon contraction induced by acetylcholine chloride 1.76×10−4 Mol (p>0.005), has not statistically significant compared to that of atropine sulfate 6.95×10−3mg/Ml (105.7292±0.8161). Conclusion: EAFTL has relaxing effect on the smooth muscle of the colon.